Neck Hematoma after Central Venous Catheterization and Awake Intubation as Rescue Airway Management Technique: A Case Report - Matea Mrčelić; Renata Curić Radivojević; Marina Kljaković-Gašpić Batinjan (Acta Clinica Croatica, 2023)
Central venous catheterization (CVC) of the internal jugular vein is an invasive procedure commonly performed in anesthesiology practice. Usually it is an uneventful procedure but complications such as bleeding, infection, and potential damage to the surrounding structures can occur. One of the complications is neck hematoma, which can distort airway anatomy and cause upper airway obstruction. We present a patient who underwent endovascular mitral valve repairment procedure under general anesthesia. Accidental puncture of carotid artery occurred while attempting to place the central line. Later, during awakening in the coronary intensive care unit, the patient developed neck hematoma. The diagnosis was confirmed with multi-slice computed tomography (MSCT) and MSCT angiography showed active arterial blood extravasation. Despite it, the patient was extubated. Awake tracheal intubation (ATI) with video laryngoscopy was the technique of choice for reintubation because of the neck swelling and compression onto laryngeal structures. In this case, rushed extubation put the patient at risk. Video laryngoscopy ATI with appropriate preparation and titrated sedation can enable quick and safe rescue airway management in patients with rapidly developing neck hematoma, along with definitive evacuation and treatment.